2015
DOI: 10.1111/dar.12323
|View full text |Cite
|
Sign up to set email alerts
|

Substituting cannabis for prescription drugs, alcohol and other substances among medical cannabis patients: The impact of contextual factors

Abstract: The finding that cannabis was substituted for all three classes of substances suggests that the medical use of cannabis may play a harm reduction role in the context of use of these substances, and may have implications for abstinence-based substance use treatment approaches. Further research should seek to differentiate between biomedical substitution for prescription pharmaceuticals and psychoactive drug substitution, and to elucidate the mechanisms behind both. [Lucas P, Walsh Z, Crosby K, Callaway R, Belle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(79 citation statements)
references
References 31 publications
7
71
1
Order By: Relevance
“…One recent study also reported reduced opioid use frequency among people who inject drugs in California who also used marijuana compared to who did not (Kral et al, 2015). However, the potential role of medical marijuana use as a harm reduction approach among opioid-using populations is still under debate and requires more research (Lucas et al, 2016). Anglin et al (Anglin, Almog, Fisher, & Peters, 1989) and Almog et al (Almog, Anglin, & Fisher, 1993) found an inverse relationship between alcohol use and heroin use among heroin dependent individuals in opioid treatment programs in California and the pattern was evident in addiction, treatment and post-discharge stages of individuals’ drug use career (Anglin, et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…One recent study also reported reduced opioid use frequency among people who inject drugs in California who also used marijuana compared to who did not (Kral et al, 2015). However, the potential role of medical marijuana use as a harm reduction approach among opioid-using populations is still under debate and requires more research (Lucas et al, 2016). Anglin et al (Anglin, Almog, Fisher, & Peters, 1989) and Almog et al (Almog, Anglin, & Fisher, 1993) found an inverse relationship between alcohol use and heroin use among heroin dependent individuals in opioid treatment programs in California and the pattern was evident in addiction, treatment and post-discharge stages of individuals’ drug use career (Anglin, et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of differences in group co-variates based on the multivariate analysis results, the MCU group reported higher disability scores after controlling for potential confounders. This likely reflects the fact that MCUs commonly feature severe overall health problems, as documented by several North American studies [13,30,31,32], including (often multiple) chronic physical and/or mental conditions. These chronic conditions are often indicated as the reason for medical cannabis use.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies conducted in the general US adult samples (Compton et al, 2007; Eaton et al, 2012), sex differences in the prevalence of behavior health disorders were not seen in medical marijuana user groups, with the exception of MDE among medical only users. The magnitude of sex differences may be attenuated by use of medical marijuana as a psychopharmacological treatment for mental problems or a substitute for alcohol or drugs (Lucas et al, 2016; Reiman, 2007, Reiman, 2009, Walsh et al, 2013; Webb and Webb, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous findings (Compton et al, 2017), medical use only was negatively associated with drug or alcohol use disorders and unmet need for drug use disorder treatment among both males and females. This is probably due to use of medical marijuana as a substitute for alcohol or other drugs (Lucas et al, 2016; Reiman, 2007; Reiman, 2009), which might be related to reduction in alcohol use and alcohol-related problems (Mikuriya, 2004). Medical use only was also negatively associated with opioid use disorder among females.…”
Section: Discussionmentioning
confidence: 99%